2020
DOI: 10.1371/journal.pone.0244153
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of insect chitosan on Salmonella Typhimurium, Escherichia coli O157:H7 and Listeria monocytogenes survival

Abstract: The antimicrobial capability of chitosan from Tenebrio molitor as compared with chitosan from crustacean (Penaeus monodon) on different pathogenic microorganisms of concern in food safety was studied. The antimicrobial effect was tested at pH 5 and pH 6.2 and at two different initial concentrations (103 or 106 CFU/mL). Results indicated that chitosan from both sources have antimicrobial activity, although the effect depended on the microorganism considered (Salmonella Typhimurium, Listeria monocytogenes and Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Pathogenic microorganisms as Listeria monocytogenes , Salmonella Typhimurium or Escherichia coli ( E. coli ) O157:H7 are of concern under the point of view of food safety. Those microorganisms are present in a broad range of foodstuffs contributing every year to large transmission of food borne illnesses [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic microorganisms as Listeria monocytogenes , Salmonella Typhimurium or Escherichia coli ( E. coli ) O157:H7 are of concern under the point of view of food safety. Those microorganisms are present in a broad range of foodstuffs contributing every year to large transmission of food borne illnesses [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tenebrio molitor chitosan was contrasted to crustacean chitosan (Penaeus monodon) for antimicrobial capability against various pathogenic microorganisms of interest in food security. Pathogenic bacteria, Salmonellasp and was found to be by far the most resistant bacteria, and insect-derived chitosan was less effective than crustacean-derived chitosan, particularly against Salmonellasp [137,138]. Insects are a credible alternative source of chitin, but due to scarcity, they have not been used in the past.…”
Section: Chitosan From Insect Sourcesmentioning
confidence: 99%
“…Deacetylation of chitin, which is found in the exoskeletons of crustaceans and insects, as well as in the cell walls of many of these fungi and some algae, is used to make chitosan on a large scale [139]. Though its main source of chitin is crab, prawn, crayfish, and shrimp residues [139], insect chitosan is essential because insects serve as a reliable source of protein [138]. This means that commercial insect processing will not only solve the problem of having a reliable source of chitin and chitosan, but it will also solve the problem of having a reliable source of chitin and chitosan.…”
Section: Chitosan From Insect Sourcesmentioning
confidence: 99%
“…Chitosan derived from two different grasshopper species were found to have a MBC of 0.32 and 0.63 mg/mL against L. monocytogenes. Another study quantified the effect of mealworm (Tenbrio molitor) and crustacean-derived chitosan on cell counts of foodborne pathogens E. coli O157:H7, L. monocytogenes and Salmonella enterica serovar Typhimurium, over 48 h [61]. The study found in general that crustacean and insect chitosan antibacterial activity at 1.5 mg/mL led to unchanged or reduced following 24 h after inoculation for all three bacteria, with recovery of bacterial counts detected between 24 and 48 h (when inoculated with 10 6 cfu/mL, pH 6.2).…”
Section: Antimicrobial Activitymentioning
confidence: 99%